Trimodal therapy for invasive bladder cancer: is it really equal to radical cystectomy?. Issue 5 (September 2015) - Mathieu, Romain; Lucca, Ilaria; Klatte, Tobias; Babjuk, Marko; Shariat, Shahrokh F.
Abstract : Purpose of review: Trimodal therapy (TMT) is considered the most effective bladder-sparing approach for muscle-invasive urothelial carcinoma of the bladder (MIBC) and an alternative to radical cystectomy. The purpose of this article was to review and summarize the current knowledge on the equivalence of TMT and radical cystectomy based on the recent literature. Recent findings: TMT consists of a maximal transuretral resection of the bladder, followed by a concurrent radiotherapy and chemotherapy, limiting salvage radical cystectomy to nonresponder tumors or muscle-invasive recurrence. In large population studies, less than 6% of the patients with nonmetastatic MIBC receive a chemoradiation therapy and this rate is stable. A growing body of evidence exists that TMT provides good oncologic outcomes with low morbidity when compared with radical cystectomy. TMT requires, however, a close follow-up because of the high risk of local recurrence and salvage radical cystectomy in up to 30% of the patients. Salvage radical cystectomy can be performed with adequate results but does not offer the same opportunity of reconstruction and functional outcomes than primary radical cystectomy. Summary: Although radical cystectomy is still the treatment of reference for most of the patients with localized MIBC, TMT represents a reasonable alternative in highly selected patients. Any firm conclusion on the equivalence or superiority of one treatment to the other is still limited by the lack of randomized controlled trials and the heterogeneity of the available literature. Future studies and multidisciplinary approach are mandatory to optimize the patient selection and regimen of TMT.